Pengembangan Assessment as learning berbasis Strategi Metakognitif ISCACoRe untuk meningkatkan kemampuan pemecahan masalah - Desy Widaningrum; Budi Naini Mindyarto; Mahardika Prasetya Aji (Postgraduate, University of Mataram, 2023)
The purpose of this study is to develop an evaluation instrument for Dynamic Fluid materials with characteristics based on the ISCACoRe metacognitive strategy and determine the quality of the instrument to improve physics problem-solving skills. This study used research and development methods. The subjects of this developing study were 11th grade students at a senior high school in Yogyakarta. The ISCACoRe metacognitive strategy-based physics learning evaluation instrument was prepared in flip modules using the assessment-as-learning model, with characteristics of being independent, flexible, stimulating, and based on digital media. The instrument's validity is 86.25%, and the assessment as learning model's validity is 93.34%, indicating that the expert instrument is appropriate for use in learning evaluation activities. The level of an item's internal consistency is declared valid if > 0.3961, a total of 8 items are accepted because > 0.3961, and 2 items are rejected because < 0.3961. The Cronbach's alpha method of 0.817 and split-half of 0.875, with very high criteria, were used to obtain the results of the instrument reliability test. The experimental and control group obtained an average score of the normalized gain test (N-Gain) of 56.83%, and 44.10% respectively